18F-FDG PET/MRI in the diagnosis of an infected aortic aneurysm - Sailer, Anna M.; Bakers, Frans C.; Daemen, Jan W.; Vöö, Stefan (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
We report a case where an integrated whole body 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/magnetic resonance imaging (MRI) is performed in the diagnostic work-up of a saccular aortic aneurysm. The integrated whole body 18F-FDG PET/MRI study answered all relevant diagnostic questions, clearly marking an infected aortic aneurysm, depicting the extent of the infected area in relation to the aortic branch vessels, and indicating the aortic lesion as the primary site of infection. The patient was successfully treated by open type V TAAA repair and pericardial graft replacement. Aortic wall infection was proven in cultures of the surgical specimen.